Layered double hydroxide as a potent non-viral vector for nucleic acid delivery using gene-activated scaffolds for tissue regeneration applications - Nicolosi, Valeria (My University, 2020)
Nonviral vectors offer a safe alternative to viral vectors for gene therapy applications, albeit typically exhibiting lower transfection efficiencies. As a result, there remains a significant need for the development of a nonviral delivery system with low cytotoxicity and high transfection efficacy as a tool for safe and transient gene delivery. This study assesses MgAl-NO3 layered double hydroxide (LDH) as a nonviral vector to deliver nucleic acids (pDNA, miRNA and siRNA) to mesenchymal stromal cells (MSCs) in 2D culture and using a 3D tissue engineering scaffold approach. Nanoparticles were formulated by complexing LDH with pDNA, microRNA (miRNA) mimics and inhibitors, and siRNA at varying mass ratios of LDH:nucleic acid. In 2D monolayer, pDNA delivery demonstrated significant cytotoxicity issues, and low cellular transfection was deemed to be a result of the poor physicochemical properties of the LDH–pDNA nanoparticles. However, the lower mass ratios required to successfully complex with miRNA and siRNA cargo allowed for efficient delivery to MSCs. Furthermore, incorporation of LDH–miRNA nanoparticles into collagen-nanohydroxyapatite scaffolds resulted in successful overexpression of miRNA in MSCs, demonstrating the development of an efficacious miRNA delivery platform for gene therapy applications in regenerative medicine.
Keywords: gene therapy applications; Biomaterials; Scaffold; Nonviral vector; Gene therapy; Layered double hydroxide; microRNA; siRNA; Plasmid DNA; Drug delivery